(untitled) - Zara Naseer; Eman Tahir; Yasmeen Qadir; Arooj Riaz (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2023)
In Pakistan, little is known about learners’ autonomous learning, especially at in Southern Punjab. To properly take into account the benefits of this learning style for learners of ESL, it is essential to comprehend their preparedness for self-directed learning in order to advance their English learning abilities. The current investigation used a survey methodology to investigate pupil’s level of self-directedness and willingness to use self-directed learning in order to improve their English learning capabilities. A total of 100 students of BS program filled out a questionnaire. The collected data was analyzed through descriptive statistics. The results demonstrated that almost all of the pupils had a fair amount of self-directedness, with little distinction between them and the exceptionally gifted kids. The outcome of the study showed that participants’ preparedness to integrate self-directed learning into their English learning as foreign language had a positive correlation with their level of self-directedness.